Ethics, Responsibility, and Sustainability in Business : Travel Insurance Assistance Companies - Elvir Ramirez, Luis Enrique; Lisa, Aleš, 1956-; Dvořák, Antonín; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
Finding the link between ethical, sustainable, and responsible business practices and their application, particularly in travel insurance help firms, is the major goal of this master's thesis. The following thesis will make an effort to address the following issues: why discuss travel insurance help; why are travel insurances currently a hot topic; and how the aforementioned procedures apply and work in this setting. An empirical analysis of the language will be part of this, and it will conclude with a case study that will help people understand why the travel insurance industry needs to employ moral, accountable, and sustainable business methods. This will demonstrate how crucial ethical behavior is in the travel insurance industry and how, when used properly, it can help these companies deliver higher-quality services. Honesty, transparency, punctuality, and confidentiality are some of the most significant results in this case study, and they will highlight the significance of these principles when it comes to giving appropriate service when needed.
Vedoucí práce: Aleš Lisa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses